Some issues of geomorphology to serve coastal environmental management of Quang Nam province - Binh, Tran Van; Mau, Le Dinh; Phai, Vu Van (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents the results of studies on the coastal geomorphological processes, which have been happening, to serve the coastal environmental management of Quang Nam province. Research results show that the geomorphological process is mainly destruction or coastal erosion, which has been occurring in most of the shores formed by loose material. In particular, coastal erosion has occurred strongly on the beaches of Cua Dai ward (Hoi An), in the south of Cua Dai (Duy Xuyen) and the south of Cua Lo (Nui Thanh). On the other hand, using geomorphological research methods, in the study area, we have determined five different geomorphic units belonging to the nearshore seabed. Thus, the zonation is carried out for risk warning according to different levels of risk of geomorphological hazards. This can help managers get a general picture for planning as well as have a specific planning policy for each coastal region in the coastal strip of Quang Nam province.